In her father's eyes : a childhood extinguished by the Holocaust - Weichherz, Béla (Rutgers University Press, 2008)
A noted historian writes her memoirs which Depict the destruction of European Yiddish culture during World War II. The author describes the cultural life she knew in Vilna as she studied at Vilna scientific Institute ... She describes her encounters with the Jewish community already feeling the rising wave of anti-Semitism which would ultimately lead to its destruction. Dawidowicz fled Poland less than 7 days prior to the arrival of German troops ... She describes her observances of the European situation from New York (1940-1945) through her work at Yivo, and concludes with her efforts at saving the few remnants of Jewish culture left in Vilna after the war.